2017
DOI: 10.18632/oncotarget.22155
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of bFGF-expressing neural stem cells promotes cell migration and functional recovery in rat brain after transient ischemic stroke

Abstract: Cerebrovascular disease such as stroke is one of the most common diseases in the aging population, and neural stem cells (NSCs) transplantation may provide an alternative therapy for cerebral ischemia. However, a hostile microenvironment in the ischemic brain offers is challenging for the survival of the transplanted cells. Considering the neuroprotective role of basic fibroblast growth factor (bFGF), the present study investigated whether bFGF gene-modified NSCs could improve the neurological function deficit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Human basic fibroblast growth factor (bFGF), as a member of FGF family, is a critical neurotrophic factor that can promote cell proliferation, suppress apoptosis, and maintain stemness of MSCs in vitro [ 43 ]. Furthermore, bFGF has also been confirmed to enhance the proliferation and differentiation of endogenous neural progenitor cells [ 44 ]. Our previous studies have shown that bFGF accelerated the DPSCs proliferation and survival in vitro and combination of DPSCs with bFGF exhibited a much better neuronal regeneration than bFGF or DPSCs alone in repairing the central nerve injuries [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human basic fibroblast growth factor (bFGF), as a member of FGF family, is a critical neurotrophic factor that can promote cell proliferation, suppress apoptosis, and maintain stemness of MSCs in vitro [ 43 ]. Furthermore, bFGF has also been confirmed to enhance the proliferation and differentiation of endogenous neural progenitor cells [ 44 ]. Our previous studies have shown that bFGF accelerated the DPSCs proliferation and survival in vitro and combination of DPSCs with bFGF exhibited a much better neuronal regeneration than bFGF or DPSCs alone in repairing the central nerve injuries [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…This raises the question of why we were not able to see similar disparities in functional and anatomical outcomes. It has been observed in various preclinical and clinical studies that often functional outcomes are not fully translated into anatomical betterment or vice versa [39,40]; however, molecular or physiologic events responsible for such discrepancies remain elusive. Based on such findings where there is a missmatch between functional and anatomical outcomes, recent attention has focused on improving the quality of life after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to angiogenesis, studies indicate that transplantation of NSCs in the early stroke phase may benefit long-term recovery through functional neuronal replacement, either directly or through augmentation of the endogenous neurogenic response [ 70 , 214 222 ]. For instance, implantation of exogenous human fetal NSCs into the ipsilateral striatum 48 h after MCAO in rats resulted in subpopulations of engrafted cells that differentiated to neuroblasts and mature neurons at 6 and 14 weeks in addition to increased amounts of proliferating and migrating neuroblasts from the SVZ [ 216 ].…”
Section: Neural Stem Cell Transplantation For Ischemic Strokementioning
confidence: 99%
“…Transplanted hNSCs also give rise to astrocytes in the rodent brain following transient forebrain ischemia [ 214 , 219 , 220 ] and intracranial hemorrhage [ 221 ]. Transplantation of mouse NSCs into the ipsilateral striatum of rats 24 h after MCAO also augmented endogenous neurogenesis and reduced infarct volume [ 215 , 222 ]. Of note, even though limited cell replacement has been observed in studies, a considerable amount of time is required for NSCs to differentiate into functional neurons, and there is still not enough evidence that cell replacement is vital for NSC-mediated recovery.…”
Section: Neural Stem Cell Transplantation For Ischemic Strokementioning
confidence: 99%